2005
DOI: 10.1530/eje.1.01941
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro effects of statins on lymphocytes in patients with Hashimoto’s thyroiditis

Abstract: Background: Statins have apoptotic effects on many cell types. Hashimoto's thyroiditis (HT) is an autoimmune disease in which cell-mediated autoimmune mechanisms are pathogenetically involved. Objective: The aim of this study was to evaluate the in vivo effects of Simvastatin on thyroid function, lymphocyte subtypes and also to investigate the apoptotic effects of Simvastatin, Mevastatin, Pravastatin and Cerivastatin on lymphocytes from patients with HT. Methods: In the first part of the study, 11 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 52 publications
(13 reference statements)
1
36
2
2
Order By: Relevance
“…Simvastatin treatment of patients with subclinical hypothyroidism secondary to autoimmune thyroid disease led to a reduction of TSH levels, which was accompanied by an increase in free thyroid hormones . The authors of the study explained this effect by immunosuppressive and proapoptopic properties of statins.…”
Section: Discussionmentioning
confidence: 99%
“…Simvastatin treatment of patients with subclinical hypothyroidism secondary to autoimmune thyroid disease led to a reduction of TSH levels, which was accompanied by an increase in free thyroid hormones . The authors of the study explained this effect by immunosuppressive and proapoptopic properties of statins.…”
Section: Discussionmentioning
confidence: 99%
“…It may be more ideal to survey the prevalence of hypothyroidism in the population of untreated hypercholesterolemia. After we determined the study design, a study showing that treatment with statins, in particular Simvastatin, may influence thyroid function in patients with Hashimoto thyroiditis was published [44]. Two patients were being treated with Atorvastatin among the patients of overt hypothyroidism with Hashimoto thyroiditis and 4 were being treated with Atorvastatin among the patients of subclinical hypothyroidism with Hashimoto thyroiditis.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 Statins are likely to have an immune-modulatory role in thyroid autoimmunity, as in vivo and in vitro studies showed an increase in serum FT3, FT4, and concomitantly a reduction in TSH levels, while CD4+ cells and B lymphocytes rose and CD8+ cells, natural killer cells and activated T lymphocytes significantly diminished. 52 According to the authors, these results are mediated by activation of apoptosis by the statins. These findings were indirectly corroborated by another study using high-dose statin therapy and reporting a significant reduction of thyroid peroxidase antibodies (TPoAB) and a decline in thyroglobulin antibodies (TgAB) in women with Hashimoto thyroiditis.…”
Section: -Hydroxy-3-methylglutaryl Coenzyme a (Hmg-mentioning
confidence: 99%